News in pharmacology for the main medical pathologies of gestation - De Guadalupe Quintana-Coronado, María; Bravo, Coral; Álvarez-Mon, Melchor; Ortega, Miguel A.; De León-Luis, Juan A. (Frontiers in Pharmacology, 2024)
Obstetric diseases represent a highly complex medical challenge, especially regarding its clinical approach. The use of pharmacological agents during pregnancy is one of the main therapeutic alternatives in this group of patients; however, there is a general lack of knowledge about its use, efficacy, and possible adverse effects that may occur in routine clinical practice, even among medical professionals themselves. The high percentage of pregnant women who undergo drugs at some point during pregnancy, together with the developments that have occurred in recent years in the field of pharmacology, show the need for a detailed analysis that shows the existing current knowledge and helps in the clinical decision making. In this sense, the aim of this work is to conduct a review of the available scientific literature on the novelties in pharmacology for the main medical pathologies of pregnancy. Thus, the role of this field in analgesia, antibiotic therapy, digestive, respiratory, urological, psychiatric and neurological pathologies will be detailed, evaluating the indications, precautions and considerations that must be taken into account for its use.